PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENGURUS - Diana Rosanti; Rauly Sijabat; Qristin Violinda (CV. Denasya Smart Publisher, 2024)
UKM PSM Gisma is an organization operating in the arts sector at PGRI University Semarang since 2005. Therefore, there are several factors that influence the daily performance of management during a period, such as leadership style, motivation and organizational commitment. Each campus organization has specific goals and missions, which can be leadership skills development, community service, advocacy, or academic development. Achieving this goal requires a clear strategy and commitment from the organization's management. For this reason, this research aims to analyze leadership style, motivation and organizational commitment on management performance. Because this research model is very complex and the number of samples is limited, multiple linear regression analysis was implemented quantitatively. This approach ensures that there is correlation and influence of the independent variable on the dependent variable. This research uses SPSS 26 software. The results of this research state that leadership style does not have a significant effect on management performance. The results of this study state that motivation has a significant effect on management performance. The results of this study state that organizational commitment has a significant effect on management performance. Organizations are expected to pay attention to the needs and desires of management in supporting the achievement of optimal performance.